(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This work discusses the prospects and advantages of using modular teaching technologies in teaching chemistry in the school system. Modular education is a flexible, structured approach in which the educational material is logically divided into complete modules, each of which is aimed at achieving specific educational goals. The work analyzes the features of developing chemistry modules, the principles of their implementation in the educational process, as well as the impact of this approach on the formation of students’ cognitive activity, the development of their independence and increasing their motivation to study science. Special attention is paid to the integration of modular technologies with modern digital teaching tools. In addition, the work presents the results of a pedagogical experiment confirming the effectiveness of modular teaching in increasing the level of mastery of chemical knowledge by schoolchildren